Relationship Between Headache and Lifestyle Among Children and Adolescents (Journal of Rangpur Medical College, 2025)
Background: Headaches are a common issue among children, affecting their daily functioning and quality of life. Objective: This study aimed to explore the distribution of headaches in children, examining factors such as age, sex, BMI, dietary habits, sleep patterns, and potential triggers. Methods: A cross-sectional study was conducted on 245 children aged 7 to 30 minutes,